Microsurgery for Brachial Plexus Injury Before Versus After 6 Months of Age: Results of the Multicenter Treatment and Outcomes of Brachial Plexus Injury (TOBI) Study. (5th February 2020) - Bauer, Andrea S.; Kalish, Leslie A.; Adamczyk, Mark J.; Bae, Donald S.; Cornwall, Roger; James, Michelle A.; Lightdale-Miric, Nina; Peljovich, Allan E.; Waters, Peter M.; Foad, Mohab; Hentz, Vincent R.; Little, Kevin; et al.
Abstract : Background: Infants with more severe brachial plexus birth injury (BPBI) benefit from primary nerve surgery to improve function. The timing of the surgery, however, is controversial. The Treatment and Outcomes of Brachial Plexus Injury (TOBI) study is a multicenter prospective study with the primary aim of determining the optimal timing of this surgical intervention. This study compared outcomes evaluated 18 to 36 months after "early" microsurgery (at <6 months of age) with the outcomes of "late" microsurgery (at >6 months of age). Methods: Of 216 patients who had undergone microsurgery, 118 were eligible for inclusion because they had had a nerve graft and/or transfer followed by at least 1 physical examination during the 18 to 36-month interval after the microsurgery but before any secondary surgery. Patients were grouped according to whether the surgery had been performed before or after 6 months of age. Postoperative outcomes were measured using the total Active Movement Scale (AMS) score as well as the change in the AMS score. To address hand reinnervation, we calculated a hand function subscore from the AMS hand items and repeated the analysis only for the subjects with a Narakas grade of 3 or 4. Our hypothesis was that microsurgery done before 6 months of age would lead to better clinical outcomes than microsurgery performed after 6 months of age. Results: Eighty subjects (68%) had early surgery (at a mean age of 4.2 months), and 38 (32%) had late surgery (at a mean age of 10.7 months and a maximum age of 22.0 months). Infants who underwent early surgery presented earlier in life, had more severe injuries at baseline, and had a significantly lower postoperative AMS scores in the unadjusted analysis. However, when we controlled for the severity of the injury, the difference in the AMS scores between the early and late surgery groups was not significant. Similarly, when we restricted our multivariable analysis to patients with a Narakas grade-3 or 4 injury, there was no significant difference in the postoperative AMS hand subscore between the early and late groups. Conclusions: This study suggests that surgery earlier in infancy (at a mean age of 4.2 months) does not lead to better postoperative outcomes of BPBI nerve surgery than when the surgery is performed later in infancy (mean age of 10.7 months). Level of Evidence: Prognostic Level II . See Instructions for Authors for a complete description of levels of evidence.